AB1243 OBESITY, METABOLIC SYNDROME AND OTHER COMORBIDITIES: INFLUENCE ON RHEUMATOID ARTHRITISAND PSORIATIC ARTHRITIS ACTIVITY AND QUALITY OF LIFE. (June 2019) - Azevedo, Soraia; Faria, Daniela; Silva, Joana; Rodrigues, Joana; Neves, Joana; Peixoto, Daniela; Tavares-Costa, José; Alcino, Sérgio; Afonso, Carmo; Teixeira, Filipa
Abstract : Background: Patients with rheumatic inflammatory conditions have an increased risk of premature death due to cardiovascular causes. It can be explained by the unfavourable interaction between the inflammatory process and the traditional cardiovascular risk factors. In obesity, especially if visceral, and in rheumatic diseases, there is production of pro-inflammatory cytokines, which contributes to an increase in cardiovascular risk. The influence of body mass index (BMI) on the evolution, activity and quality of life in rheumatoid arthritis (RA) and in psoriatic arthritis (PsA) has been proven. However, studies evaluating the influence of the abdominal circumference (AC) and metabolic syndrome (MS) are meagre. Objectives: To assess the influence of BMI, AC and MS, on disease activity and quality of life in RA and PA, using parameters of inflammatory activity (sedimentation rate (SR) and C-reactive protein (CRP), Activity Score (DAS28), Visual Analogue Pain Scale (VAS) and Health Assessment Questionnaire (HAQ) and to compare patients with RA and PA. Methods: A cross-sectional study, including 150 patients with RA, diagnosed according to the ACR/EULAR criteria and 75 patients with PsA (CASPAR criteria). Assessment of weight, height, AC, SR and CRP of all patients, clinical and demographic data collection. The presence of MS was assessed according to WHO definition. Participants completed HAQ and disease activity was measured by DAS28. SPSS was used for the statistical analysis, significance level was 2-sided p<0.050. Results: Age, duration of illness, schooling and professional class were similar in RA and PsA. In RA there was a predominance of females (78.7%), while in PsA a predominance of males (53.3%). There were no differences between the quality of life (by HAQ), or in the disease activity (by DAS28 or by inflammatory parameters). PsA patients had significantly higher BMI and AC. The number of comorbidities was higher in cases of PsA. Dyslipidaemia and hyperuricemia were significantly more frequent in this group of patients. Independently the underlying pathology (RA or PsA), the number of comorbidities correlated positively with DAS28, with HAQ, CRP and SR. In RA group, there was a positive correlation of both BMI and AC with HAQ, also MS associated the highest HAQ values. Overweight/obesity (BMI≥25kg/m 2 ) were associated with at least one painful joint. Still, the risk of having at least one swollen joint was 3.4 times higher in patients with increased AC (95% CI: 1.08-10.39). There was an association between the BMI and AC and the CRP value. Patients with BMI≥25 kg/m 2 and with increased AC had DAS28 values significantly higher. MS was associated with significantly higher SR. In PsA group Patients with MS had higher CRP values, more joint pain and higher disease activity according to DAS28. Patients with BMI≥25kg/m 2 also had more painful joints and higher CRP values. None of the patients with normal BMI had swollen joints, however 20.4% of overweight patients had at least one swollen joint. There was no association between the disease phenotype and BMI, AC or MS. Conclusion: In this study there was a higher prevalence of classic cardiovascular risk factors in patients with PsA. The number of comorbidities showed to influence inflammatory parameters, disease activity and quality of life. We found that BMI, AC and MS are associated with disease activity, which may be improved by weight reduction and control of comorbidities. Therefore they should be considered in the treatment of rheumatologic diseases. References: [1] Avina-Zubieta J. A. et al [2] Ursini, F. et al. [3] Wei S. T et al. [4] Azfar RS et al. [5] Eder L. et al. [6] Souza CS et al. [7] Clavelab G. et al. [8] George MD et al. [9] Vidal C. T. et al. [10] Frazier-Mironer A. Disclosure of Interests: None declared